Geometric Patterns in the Hena Puan Traditional House as a Context for Ethnomathematics Based Mathematics Learning - Asria Ratau; Arien Sayang (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This study aims to examine the geometric concepts embedded in the Baeleo Hena Puan traditional house as a context for ethnomathematics-based mathematics learning. The research employs a qualitative approach with an exploratory descriptive method through visual analysis of the architectural structures of the traditional house. The results of the analysis indicate that the Baeleo Hena Puan traditional house incorporates various geometric concepts, including two-dimensional shapes such as rectangles, triangles, and trapezoids, as well as three-dimensional solids in the form of rectangular prisms and triangular prisms. In addition, patterns of repetition and reflectional symmetry were identified in the arrangement of columns and building openings. From the perspective of D’Ambrosio’s ethnomathematics, these findings represent mathematical activities that have developed within the cultural practices of the local community. The integration of traditional architecture as a context for mathematics learning has the potential to bridge formal mathematics with students’ cultural experiences, thereby supporting meaningful, contextual, and culturally inclusive learning. This study recommends the use of the Baeleo Hena Puan traditional house as a contextual learning resource in geometry instruction at schools